(untitled) (SciELO Preprints, 2022)
Amazonian phlebotomine fauna is considered one of the most diverse in the world. In addition, the region is the most prevalent for leishmaniasis in Brazil and South America. The state of Acre, which belongs to this region, also stands out in terms of the diversity of the sand fly fauna, as well as the occurrence of American tegumentary leishmaniasis. In this context, the present Dataset comprise a bibliographic review of sand fly species recorded in Acre State, Amazon region, Brazil. A total of 1,096 observations from Material Citation type (and two of preserved specimens) were presented using 32 variables according to Darwin Core terms. The bibliographic review was performed in PubMed, Google Scholar, SciELO, BVS (Biblioteca Virtual em Saúde) and bibliographic references cited in related scientific articles. Thus, the present study is a solid report for further studies on sand fly studies in Acre and other Amazon states.